Understanding students’ game experiences throughout the developmental process of the Number Navigation Game - Bui Phuong; Rodríguez-Aflecht Gabriela; Brezovszky Boglárka; Hannula-Sormunen Minna M.; Laato Samuli; Lehtinen Erno (Springer Nature, 2022)
Serious games for learning have received increased attention in recent years. However, empirical studies on students’ gaming experiences throughout the developmental process of serious games and discussions regarding game design are missing. The aims of the present study were to analyze students’ gaming experiences while playing four consecutive versions of the Number Navigation Game (NNG)—a mathematical game-based learning environment focusing on flexibility and adaptivity with whole-number arithmetic; and to provide an extensive review of the NNG developmental and design process over 3 years with focus on how and why the design decisions were made, and how those choices affected students’ gaming experiences. The study employed a mixed-methods design of quantitative and qualitative research. The Game Experience Questionnaire about eight core game experience dimensions was answered by different groups of students at primary schools in Finland in three different experiments after students played four versions of the NNG from 2014 to 2016. Six semi structured interviews related to students’ game experiences, preferences and game features of the latest version of NNG were conducted. Overall, results indicate that improvement in game’s usability and clarity in the user interface has positive impacts on students’ game experiences. Furthermore, there seems to be a clear advantage in having better aesthetics and value in improving extrinsic elements that could contribute to maintain players’ enthusiasm and situational interest in serious games.